2022
DOI: 10.1088/1748-9326/ac9422
|View full text |Cite
|
Sign up to set email alerts
|

Long-term trends of impacts of global gasoline and diesel emissions on ambient PM2.5 and O3 pollution and the related health burden for 2000–2015

Abstract: Global economic development and urbanization during the past two decades have driven the increases in demand of personal and commercial vehicle fleets, especially in developing countries, which has likely resulted in changes in year-to-year vehicle tailpipe emissions associated with aerosols and trace gases. However, long-term trends of impacts of global gasoline and diesel emissions on air quality and human health are not clear. In this study, we employ the Community Earth System Model (CESM) in conjunction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
(81 reference statements)
0
7
0
Order By: Relevance
“…44 We ran the (supplemental text S1). Further details on CAM6-Chem model configuration and evaluation have been described explicitly on our previous study 5 and elsewhere. 44,[47][48][49] Health Risk Assessment…”
Section: Model Simulationmentioning
confidence: 99%
See 3 more Smart Citations
“…44 We ran the (supplemental text S1). Further details on CAM6-Chem model configuration and evaluation have been described explicitly on our previous study 5 and elsewhere. 44,[47][48][49] Health Risk Assessment…”
Section: Model Simulationmentioning
confidence: 99%
“…To better interpret global trends of health burdens associated with HVOC exposure, we divided the continent of the world into 11 regions 5,6 : China, India, ROA, LATIN, SSA, ECEurope, NAME, the US, Canada, WEurope and ROW. The former seven regions are classified as developing countries, while the latter four are developed countries, in accordance with the International Monetary Fund classficiation.…”
Section: Model Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Ground‐level ozone (O 3 ) in urban areas is of great interest to regulatory and scientific agencies due to its adverse effects on human health and natural ecosystems (Avnery et al., 2011; Feng & Kobayashi, 2009; Huang et al., 2021; McDonnell et al., 1999; Neidell, 2009; Xiong et al., 2022) as well as its long atmospheric lifetime (global mean: 22 days) (Stevenson et al., 2006). Findings from extensive observational and modeling studies suggested that locally produced O 3 can be transported over distances of hundreds of kilometers from source regions, leading to transboundary and intercontinental pollution problems (Akimoto, 2003; Holloway et al., 2003; Wilkening et al., 2000; Xiong et al., 2020).…”
Section: Introductionmentioning
confidence: 99%